2021
DOI: 10.3390/ijms22052713
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide Synthase 2 Null Mice Are Protected from Ovalbumin-Induced Asthma with Higher T Cell Receptor Signal Strength in CD4+ T Cells

Abstract: (1) Background: six mammalian ceramide synthases (CerS1–6) determine the acyl chain length of sphingolipids (SLs). Although ceramide levels are increased in murine allergic asthma models and in asthmatic patients, the precise role of SLs with specific chain lengths is still unclear. The role of CerS2, which mainly synthesizes C22–C24 ceramides, was investigated in immune responses elicited by airway inflammation using CerS2 null mice. (2) Methods: asthma was induced in wild type (WT) and CerS2 null mice with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…These results suggest that activated Th cells upregulate CerS2 expression to produce Cer (d18:1/24:0) for glycosphingolipid biosynthesis, including HexCer (d18:1/24:0) and DiHexCer (d18:1/24:0). Importantly, a previous study reported that mice de cient in CerS2 exhibited reduced sensitivity to ovalbumin-induced allergic asthma, accompanied by impaired Th2 responses 23 . Upon antigen stimulation, the TCR aggregates into plasma membrane domains known as lipid rafts, which primarily comprise sphingolipids, glycosphingolipids, cholesterol, and phospholipids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that activated Th cells upregulate CerS2 expression to produce Cer (d18:1/24:0) for glycosphingolipid biosynthesis, including HexCer (d18:1/24:0) and DiHexCer (d18:1/24:0). Importantly, a previous study reported that mice de cient in CerS2 exhibited reduced sensitivity to ovalbumin-induced allergic asthma, accompanied by impaired Th2 responses 23 . Upon antigen stimulation, the TCR aggregates into plasma membrane domains known as lipid rafts, which primarily comprise sphingolipids, glycosphingolipids, cholesterol, and phospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…Upon antigen stimulation, the TCR aggregates into plasma membrane domains known as lipid rafts, which primarily comprise sphingolipids, glycosphingolipids, cholesterol, and phospholipids. The impairment of downstream TCR signaling in CerS2 or CerS6 de cient CD4 + T cells highlights the importance of Cer for the regulation of TCR stimulation 22,23 . However, detailed investigations are necessary to elucidate the speci c roles of Cer, HexCer, and DiHexCer in the regulation of TCR stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…CerS2 knockout mice were less sensitive against Ovalbumin-induced allergic asthma which was accompanied by an impaired Th2 response and increased Th17 response. Notably, the increased Th17 response was only visible after TCR stimulation, indicating that loss of very-long chain ceramides in CerS2 knockout mice affects TCR signalling in Th17 cells ( Table 1 ) ( Shin et al, 2021 ). However also CerS4, CerS5 and CerS6 affect TCR signalling, although in different ways.…”
Section: The Impact Of Sphingolipids On T Cells and Their Role In Res...mentioning
confidence: 99%
“…In the murine study, CD4 + T cells increase the transcription of CerS2, CerS4, CerS5 and CerS6 when stimulated with anti-CD3/CD28 antibodies while CD4 + T cells from CerS2 null mice show lower levels of these CerSs than WT cells ( 34 ). CerS2 deficiency enhances TCR signal strength as compared to WT control in activated CD4 + T cells, which is reflected by increased phosphorylation of extracellular-regulated kinase (ERK) and AKT.…”
Section: Ceramide Metabolismmentioning
confidence: 99%
“…CerS2 deficiency enhances TCR signal strength as compared to WT control in activated CD4 + T cells, which is reflected by increased phosphorylation of extracellular-regulated kinase (ERK) and AKT. The increased TCR signal induced by CerS2 deficiency further promotes the differentiation of CD4 + T cells towards Th17, but away from Th2 ( 34 ). Different from the proinflammatory responses of CerS2 knockout in CD4 + T cells, transfer of CerS6-deficient CD4 + T cells induced less colitis compared to WT cells ( 35 ).…”
Section: Ceramide Metabolismmentioning
confidence: 99%